Aljdhiran incision and rip and derivatives in the Qur'an: A statistical study morphological tag (Journal of the College of Education for Women, 2019)
It is more beneficial science and created and the highest honor is the Koran Sciences, God has honored research in this fun science, came this research that shed the light on the radical incision, and Naughty derivatives as contained in the Koran, and illustrate the diversity of Saghma morphological, and fork them from derivatives what it entailed connotations, as well as the evacuation of cryptic in some of these verses from the biological secrets take minds newly exposed Anitrjt science under the name of scientific miracles.The research methodology is revenue verse which included the word, and revenue lexical meaning and its meaning in the context of the Qur'an, and reflect the views of the commentators of the verse, and then the relationship of that science and reflect the opinion of the researcher to ask for it, and a variety of sources on the written language and grammar, rhetoric and interpretation. And the God of the intent behind.